2020
DOI: 10.1149/2162-8777/ab80af
|View full text |Cite
|
Sign up to set email alerts
|

PECVD Growth of Composition Graded SiGeSn Thin Films as Novel Approach to Limit Tin Segregation

Abstract: SiGeSn is a promising group IV material to develop the field of silicon photonics. Increasing the tin concentration in the alloy is desired in order to achieve a direct bandgap in the material. This necessitates low temperature growth and proper strain management in the films during growth to prevent tin segregation. In this work, plasma enhanced chemical vapor deposition (PECVD) was used to grow composition graded SiGeSn films at low processing temperatures of 350 °C-380 °C using a simplified PECVD reactor. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, there has yet to be a review article that systematically reported on GeSn material growth and counterpart optoelectronic devices using the CVD technique. UHVCVD [ 101 , 102 , 103 , 104 ], RPCVD [ 105 , 106 , 107 , 108 , 109 , 110 ], PECVD [ 111 , 112 , 113 ], LPCVD [ 114 , 115 , 116 , 117 ], and APCVD [ 118 , 119 ] are discussed in this review, with a focus on identifying processes that can be transferred for the commercial production of GeSn. The objective of this comprehensive review article is to provide readers with a full understanding of the recent experimental advancements in GeSn material growth using CVD, as well as their optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there has yet to be a review article that systematically reported on GeSn material growth and counterpart optoelectronic devices using the CVD technique. UHVCVD [ 101 , 102 , 103 , 104 ], RPCVD [ 105 , 106 , 107 , 108 , 109 , 110 ], PECVD [ 111 , 112 , 113 ], LPCVD [ 114 , 115 , 116 , 117 ], and APCVD [ 118 , 119 ] are discussed in this review, with a focus on identifying processes that can be transferred for the commercial production of GeSn. The objective of this comprehensive review article is to provide readers with a full understanding of the recent experimental advancements in GeSn material growth using CVD, as well as their optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…PECVD enabled low substrate temperatures and high deposition rates by providing additional energy for precursor bond dissociation through collisions with plasma ions. The effect of temperature and con-centration grading were discussed in prior manuscripts [29] [30]. The focal point of this manuscript is the effect of the substrate type on the SiGeSn film properties.…”
Section: Introductionmentioning
confidence: 99%
“…due to a high plasma density and a low ion bombardment energy which are conducive to achieving reasonable processing rate and less damage to the substrate. [1][2][3] Some researches [4] have shown that the high driving frequency of capacitively coupled plasma (VHFCCP (30 MHz-300 MHz)) system has some advantages over traditional 13.56-MHz capacitive discharge, which can generate unique gas-phase chemistry and have different processes of excitation, dissociation, and ionization. [5] These sources are beneficial to controlling the morphology of film.…”
Section: Introductionmentioning
confidence: 99%